(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The ethical and environmental aspects of animal-based food production have become increasingly relevant in global discourse, particularly in countries like Uzbekistan, where the agricultural sector plays a significant role in economic and social development. This paper explores the ethical concerns related to animal welfare, industrial farming, and the sustainability of livestock production, alongside the environmental impact of greenhouse gas emissions, land degradation, and water consumption associated with animal agriculture. The study examines existing literature to provide a comprehensive understanding of these issues and their implications for the food industry and consumer choices. Furthermore, the paper discusses potential solutions, including sustainable farming practices, alternative protein sources, and policy interventions that could mitigate the negative effects of conventional animal-based food production.